PENGABDIAN MASYARAKAT: PENERAPAN MEDIA INTERAKTIF TYPING MASTER UNTUK MENINGKATKAN EFISIENSI BELAJAR MENGETIK SISWA SMK PAB 8 - Fahrozi, Wirhan; Ginting, Erwin; Wahyuni, Linda; Gunawan, Heri (Jurnal Pengabdian Masyarakat Berkarya, 2025)
This study aims to determine the extent to which the use of the Typing Master application can improve the efficiency of typing learning for Vocational High School (SMK) students. Ten-finger typing skills are an important competency in supporting student productivity in the digital era, especially in departments related to office administration and information technology. The research method used is quantitative with a quasi-experimental approach. The research subjects consisted of two groups: the experimental group that used Typing Master in the learning process, and the control group that used conventional methods. The results showed that the use of the Typing Master application significantly increased students' typing speed and accuracy. In addition, students became more motivated in learning because of the interactive interface and gradual practice features that were appropriate to their ability level. Thus, the Typing Master application has proven effective as a learning medium that can improve the efficiency of SMK students' typing learning.